EDGE study in Russian Federation: efficacy and safety of vildagliptine in comparison with other oral antidiabetic agents in patients with type 2 diabetes mellitus - Gagik Radikovich Galstyan (Сахарный диабет, 2013)
According to international consensus, metformin is acknowledged as a first-line therapeutic agent for type 2 diabetes mellitus (T2DM). However, in most cases this treatment eventually requires intensification by supplementation with other hypoglycemic medications. The aim of the EDGE study (Effective Diabetes control with vildaGliptin and vildagliptin/mEtformin) was to assess the efficacy and safety of vildagliptin in comparison with other oral agents in routine management of patients with T2DM that has been poorly controlled by metformin monotherapy.